CONCEPTUALIZATION OF LONG-TERM CARE POLICIES FOR THE ELDERLY POPULATION – ANALYSIS OF SERBIA'S (IN)COMPLIANCE WITH THE CHARACTERISTICS OF THE POLICIES IN THE EUROPEAN UNION - Jovanović, Vladimir (Political Review, 2023)
Long-term care policies are aimed at the most vulnerable parts of the population and are characterized by the (non)existence of opportunities, choices, alternatives, lack of (or not) the autonomy of choice, human rights, and the humanity of society. Thus, through the conception of social policies of long-term care, the social relationship towards those who are long-term dependent on other people's support in order to perform their daily activities, meet basic needs, and be socially integrated is regulated. This work focused on the analysis of the compliance of these aspects of social policy in Serbia and the European Union, using the comparative method, in relation to the indicators of the relevant areas. The subject of the research is focused on social policies and that part of them that refers to the long-term care of the elderly population. Territorial determination implies an analysis of the situation in the Republic of Serbia and the countries of the European Union. The aim of the work was to determine the similarities and differences in the basic elements of long-term care policies, and to conduct a comparative analysis in relation to the Republic of Serbia and relevant representatives of the corresponding social-political models recognized in the member states of the European Union. The paper tried to answer the question of whether there are differences in the formulation and provision of long-term care, as well as what are the similarities and differences in content, both in relation to the determined funds and the available support activities. Through the analysis, it was determined that the comparison of Serbia and EU representatives identifies that the characteristics of long-term care that are present in EU countries and Serbia indicate many differences and some similarities. The similarity is observed in the demographic indicators, as well as in the declarative determination to follow the concept of deinstitutionalization. However, the following of this concept is different in Serbia and EU countries, because the indicators show that in the EU there is a far greater number of users of services that support staying at home with help and support. In Serbia, the situation is different and the number of users of accommodation and support services in a natural environment is very similar. Also, the difference that is present in this context is in relation to the percentage of the population that uses long-term care services. In our country, that percentage is significantly lower than in EU countries. Significant differences are also observed in relation to the position and support of informal caregivers. In the Republic of Serbia, this type of support is not even normatively recognized, and institutional mechanisms do not provide any assistance to these persons. Unlike Serbia, the EU has defined various support mechanisms for this category of population.
Keywords: Long-term care; Social Policy; European Union; Elderly; Beneficiaries; Republic of Serbia